Organ printing: Tissue spheroids as building blocks() - Mironov, Vladimir (2009)
Organ printing can be defined as layer-by-layer additive robotic biofabrication of three-dimensional functional living macrotissues and organ constructs using tissue spheroids as building blocks. The microtissues and tissue spheroids are living materials with certain measurable, evolving and potentially controllable composition, material and biological properties. Closely placed tissue spheroids undergo tissue fusion — a process that represents a fundamental biological and biophysical principle of developmental biology-inspired directed tissue self-assembly. It is possible to engineer small segments of an intraorgan branched vascular tree by using solid and lumenized vascular tissue spheroids. Organ printing could dramatically enhance and transform the field of tissue engineering by enabling large-scale industrial robotic biofabrication of living human organ constructs with “built-in” perfusable intraorgan branched vascular tree. Thus, organ printing is a new emerging enabling technology paradigm which represents a developmental biology-inspired alternative to classic biodegradable solid scaffold-based approaches in tissue engineering.